AB0813 Bisphosphonate Drug Holiday from Patient Perspective - Beliefs and Attitudes. (10th June 2014) - Duna, M.; Berghea, F.; Predeteanu, D.; Balanescu, A.; Bojinca, V.; Opris, D.; Constantinescu, C.; Abobului, M.; Groseanu, L.; Saulescu, I.; Borangiu, A.; Negru, M.; et al.
Abstract : Background: Bisphosphonates are widely prescribed and highly effective at limiting the bone loss in senile osteoporosis in both men and women. Although they are generally well tolerated, potential adverse effects may limit bisphosphonate use for longer periods. In addition these drugs accumulate in bone and continue to produce a therapeutic effect – that's why the idea of a drug holiday in this case received an increasing attention during last years. While rheumatologists' reasons to support this holiday are widely presented little is known about the patients' beliefs and attitudes in this matter. Objectives: To evaluate the patients' beliefs and attitudes regarding a potential drug holiday during bisphosphonates treatment. Methods: A structured questionnaire was developed to capture demographic data, personal experience and acceptance of bisphosphonates, level of knowledge about possible drug holiday, personal beliefs and attitudes regarding such regime. Osteoporotic patients following a bisphosphonate treatment have been invited to answer the questionnaire. SPSS 19.0 have been used to perform statistical analysis. Data are presented in mean (sd) format; a p<0.05 was considered significant Results: A number of 61 subjects accepted to participate in this study. Demographic data revealed: age 64.1 (9.7) years, sex ratio (F:M) – 6:1, history of fractures in 32.8 cases, duration of bisphosphonate therapy: 3.67 (2.6) years. One third of the subjects were aware of the possibility of a drug holiday (no difference between gender, living area or education based groups). 78.7% believe that such a holiday will produce a "totally negative" and a "mainly negative" impact on the control of disease. Those who believe this holiday will have a greater impact are the same who predict a predominant negative impact – Pearson correlation index: 0, 53. Around half of the subjects (52.5%) declared them as being favorable to such a holiday, however these answers went mainly form those who believe this holiday will have a small impact on the control of disease and are ready to try this in the near future. 86.9% of the subjects expect their doctor to open such a subject. Those who are not favorable to such a holiday are ready to pay extra for the treatment (41%) or to receive a less expensive drug (42.5%). Conclusions: There is a great need for patient education regarding the potential effects of drug holiday during the treatment of osteoporosis and to respond to various concerns patients do have. A large proportion of patients have negative feelings concerning this possibility. Those patients (not so many) that feel they control the disease are the same who are ready to try this change – this raise the question whether or not the patients follow their treatment because they are more scared than informed of osteoporosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3020